2015
DOI: 10.1515/jpem-2014-0402
|View full text |Cite
|
Sign up to set email alerts
|

A patient developing anaphylaxis and sensitivity to two different GnRH analogues and a review of literature

Abstract: Gonadotropin-releasing hormone analogues are used in the treatment of prostate cancer, breast cancer, endometriosis, and uterine leiomyomas in adults and often in the treatment of precocious puberty in children. Many adverse effects have been reported for gonadotropin-releasing hormone analogues, but anaphylaxis is rarely reported as an adverse effect. Frequent cross-reactions, particularly during childhood, and diversity of the time of onset of anaphylactic manifestations complicate the diagnosis. A patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Triptorelin, a long-lasting GnRHa, decreases testosterone levels in boys and estrogen levels in girls. Triptorelin is a widely used drug with few reported adverse effects, such as erythema, bruising, pain, sterile abscesses, menopausal-like symptoms, and anaphylaxis (2, 3). So far secondary arterial hypertension (HTN) has been reported in only 3 patients with CPP (46).…”
Section: Introductionmentioning
confidence: 99%
“…Triptorelin, a long-lasting GnRHa, decreases testosterone levels in boys and estrogen levels in girls. Triptorelin is a widely used drug with few reported adverse effects, such as erythema, bruising, pain, sterile abscesses, menopausal-like symptoms, and anaphylaxis (2, 3). So far secondary arterial hypertension (HTN) has been reported in only 3 patients with CPP (46).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the structural homology of GnRH analogues and potential cross-reactivity, patients may rarely encounter allergic reactions to more than one GnRH analogue. Ökdemir et al [5] reported a CPP case with proven allergy to both LA and TA depot preparations. Similarly, 1 patient (case 1) in our cohort was reactive to both LA and TA and preferred to cease the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several types of allergic reactions to GnRH analogue treatment have been reported ranging from cutaneous adverse reactions such as urticaria, acne, alopecia, pruritus, purpuric rash, photosensitivity, injection site reactions (flare or subcutaneous nodule formation), mycosis-fungoides-like eruption to serum sickness and anaphylaxis [3,4]. However, only case reports have been presented until now and no systematic review or guideline for the management of allergic reactions to GnRH analogues is available [1,[5][6][7][8][9][10][11][12]. On the other hand, the frequency of CPP and the use of GnRH analogues has been increasing in the recent years, which warrants a proper surveillance and management of potential side effects of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylactic reactions in patients receiving this treatment are very rare. In the current literature, only few cases have been reported . We describe a girl with idiopathic central precocious puberty who showed an anaphylactic reaction after administration of GnRH analogues.…”
Section: Introductionmentioning
confidence: 91%